Institutions and economic growth: An examination of their correlation in Bosnia and Herzegovina - Amra Babajić; Mirnesa Baraković Nurikić; Nisad Karabegović (Ekonomski Vjesnik)
Purpose: Institutions play an important role in stimulating economic growth of the country. They create frameworks for economic activity through restrictions that shape human interaction. Economic growth is a complex process influenced by many factors, including the quality of institutions. The main goal of this paper is to examine the correlation between institutions and economic growth in Bosnia and Herzegovina (hereinafter referred to as B&H). Methodology: The paper applies both descriptive and inferential statistics, along with various scientific research methods. It examines the correlation between selected indicators and conducts regression analysis to establish the relationship between indicators of economic growth and the institutional quality in Bosnia and Herzegovina during the period from 2002 to 2022. The central research question is: Does institutional quality determine economic growth in B&H? Specifically, which elements of institutional quality have a positive impact, and which have a negative impact on GDP? Additionally, which elements have the strongest correlation with changes in GDP in B&H? Results: Results show that institutional quality is declining, while economic growth exhibits modest positive trends. Correlation analysis revealed a statistically significant relationship between Voice and Accountability, Regulatory Quality, Rule of Law, and Control of Corruption and Economic Growth in B&H, while regression analysis further determined that Regulatory Quality has the greatest impact on economic growth in B&H. Conclusion: One of the key challenges for economically, politically, socially, and religiously complex, small, and open countries like Bosnia and Herzegovina is the development of adequate, efficient, transparent, and corruption-free institutions.